Pembentukan Pengadilan Khusus Sengketa Pelayanan Kesehatan - Arief Kresna Wira Prasdyantoro; Mohammad Zamroni (Fakultas Hukum Universitas Hang Tuah, 2023)
This study analyzed the establishment of Special Court for Health Service Disputes which is based on the occurrence of a legal vacuum and the existence of certain advantages that will be regulated in the Special Court for Health Service Disputes. The non-regulation regarding the Law on Special Courts for Health Service Disputes in Indonesia can be interpreted as a legal vacuum because a judicial institution has not been established that can enforce the law to the fullest and has legal certainty. It can also result in the emergence of injustice in society. Therefore, this study was a juridical - normative research using a legal approach and a conceptual approach. The results of the study found that the establishment of Special Court for Health Service Disputes could be performed within the scope of criminal justice and under the general court as stipulated in Article 27 of Law Number 48 of 2009 Concerning Judicial Powers which has its own characteristics which include philosophical, sociological and juridical foundations. The urgency of the establishment of special court for health service disputes was due to a legal vacuum (rechtsvacuum), the advantages of a special court for health service disputes, the specificity of the malpractice case, ad hoc judge and restitution.